2017
DOI: 10.18632/oncotarget.16146
|View full text |Cite
|
Sign up to set email alerts
|

XPGgene polymorphisms and cancer susceptibility: evidence from 47 studies

Abstract: Xeroderma pigmentosum group G (XPG) is a single-strand-specific DNA endonuclease that functions in the nucleotide excision repair pathway. Genetic variations in XPG gene can alter the DNA repair capacity of this enzyme. We evaluated the associations between six single nucleotide polymorphisms (SNPs) in XPG (rs1047768 T>C, rs2296147 T>C, rs2227869 G>C, rs2094258 C>T, rs751402 C>T, and rs873601 G>A) and cancer risk. Forty-seven studies were identified in searches of the PubMed, Scopus, Web of Science, China Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Additionally, XPC rs3731054 was associated with DFS alone. To date, none of these SNPs have been reported to be associated with ESCC survival or PBC efficacy, although two SNPs ( ERCC2 rs238406 and rs2094258) within the same LD block of the significant rSNPs were reported to be associated with ESCC survival . Our finding has further strengthened that these LD blocks may contribute to survival of Chinese ESCC patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Additionally, XPC rs3731054 was associated with DFS alone. To date, none of these SNPs have been reported to be associated with ESCC survival or PBC efficacy, although two SNPs ( ERCC2 rs238406 and rs2094258) within the same LD block of the significant rSNPs were reported to be associated with ESCC survival . Our finding has further strengthened that these LD blocks may contribute to survival of Chinese ESCC patients.…”
Section: Discussionsupporting
confidence: 57%
“…The ERCC5 rs3759497 LD block consists of 17 SNPs, among which two were predicted to be functional (Supplemental Table S4). While rs1323697 has not been associated with any type of cancer, rs2094258 has been previously reported to be associated with risk of different cancers and survival of esophageal cancer …”
Section: Resultsmentioning
confidence: 94%
“…Besides, Hua et al [ 24 ] reported that rs873601 A allele can also contribute to the susceptibility of colorectal cancer in a Southern Chinese population with a total of 1,901 cases and 1,976 controls. Two studies have performed comprehensive meta-analyses to evaluate the association of XPG polymorphism rs873601 with cancer risk: Han et al [ 25 ] found that polymorphism rs873601 was significantly associated with overall cancer risk, using data from 12 studies, including 9,158 cases and 10,073 controls focus on rs873601; while another meta-analysis study that included data from 23 reports found that this polymorphism was related to the cancer susceptibility only in Asians [ 26 ]. The ethnic and demographic differences among studies might be partly due to the enormously different frequencies of the rs873601 A allele in different groups (0.48 in Chinese, CHB; 0.53 in Caucasian, CEU; 0.30 in Africans (YRI), according to HAPMAP database, www.hapmap.org/ ).…”
Section: Discussionmentioning
confidence: 99%
“…Xeroderma pigmentosum (XP) is a rare condition characterized by an extreme sensitivity to ultraviolet (UV) rays from sunlight often causing skin burn. It affects the eyes and areas of skin exposed to the sun and is associated with an increased risk of skin cancer of lips, eyelids as well as brain tumors [ 133 ]. Patients with XP may present with neurological complications such as cerebellar ataxia, chorea, hearing loss, poor coordination, difficulty walking, movement problems, loss of intellectual function, difficulty swallowing and talking, and seizures [ 134 ].…”
Section: Xeroderma Pigmentosummentioning
confidence: 99%